Travelling with your eyes closed: the Ulysses-like experience of “Maia” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
In the summer of 1895 d’Annunzio, together with some friends, embarked on Edoardo Scarfoglio’s yacht for a holiday in Greece. The adventure turned out to be tiring and unpleasant, rather incongrous with the «vivere inimitabile». And yet, a few years later, that not very fortunate journey acquired a new dignity in Maia. D’Annunzio casts the whole adventure into an epic dimension, superimposing his own figure on that of Ulysses: a new hero who travels the sea to discover a Greekness that is not merely archeological, but one that is deeply rooted in the modern world.